2021
DOI: 10.1111/tbed.14042
|View full text |Cite
|
Sign up to set email alerts
|

A serological survey and characterization of Getah virus in domestic pigs in Thailand, 2017–2018

Abstract: Getah virus (GETV) is a mosquito‐borne RNA virus belonging to the family Togaviridae, genus Alphavirus. GETV infection causes diarrhoea and death in piglets, and reproductive failure and abortion in sows. This study conducted a serological survey of GETV infection among domestic pig populations in Thailand. ELISA was used to analyse 1,188 pig serum samples collected from 11 provinces of Thailand during 2017–2018, with 23.1% of the samples being positive for anti‐GETV antibodies. The positive ratio of anti‐GETV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…GETV is a member of the Alphavirus genus, its pathogenicity for humans is unknown, but there may be a risk of spill-over events to humans [72]. Up to now, epidemiological surveillance studies and available GETV sequences from swine have been rare [26, 73, 74]. In this study, we perform a state-of-the-art genomic surveillance using metagenomic next-generation sequencing coupled with phylodynamic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…GETV is a member of the Alphavirus genus, its pathogenicity for humans is unknown, but there may be a risk of spill-over events to humans [72]. Up to now, epidemiological surveillance studies and available GETV sequences from swine have been rare [26, 73, 74]. In this study, we perform a state-of-the-art genomic surveillance using metagenomic next-generation sequencing coupled with phylodynamic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This also means that the GIV viruses could be transmitted between the mosquitoes and vertebrate hosts in nature without being detected due to the absence of disease. In relation, the GETV/SW/Thailand/2017 of GIV group was isolated from a pig serum during a sero-surveillance in Thailand, where no disease was reported 19 . It is worth noting that the pig-origin GIV virus strain, in comparison to the mosquito-origin GIV viruses, showed an amino acid substitution at the E2 (L269V), which was exclusively associated with GIII lineage and was found to be the sole positive selection site in the structural genes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one GIV strain (GETV/SW/Thailand/2017) was isolated from a pig serum in Thailand in 2017, with no clinical signs reported 19 . Nevertheless, it remains uncertain whether the GIV viruses will be competent for epidemic spreading in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Piglets infected with GETV showed depression, tremor, hind limb paralysis, diarrhea, and high mortality ( 10 ). Histopathological examination showed that GETV-infected pigs had neurodegenerative changes (neuronophagocytosis and central chromatin dissolution), pneumocytes detachment, renal cortical thickening, hemorrhagic splenitis ( 11 ). Infected sows had abortions ( 12 ).…”
Section: Introductionmentioning
confidence: 99%